Qualitative characteristics of the water of the Tigris River for two sites in the city of Mosul (NTU Journal of Agriculture and Veterinary Science, 2024)
Changing the quality characteristics of water directly affects human health ,living organisms, physical and chemical properties of the soil, and affects crop yield. Two sites were chosen to collect samples, the first in the village of Sharekhan which is the last point through which the Tigris River passes before entering the city of Mosul, which is located northwest of the city of Mosul .The second site was in village of Al-Busif south of Mosul to compare the seasonal change in the Qualitative characteristics of the water between the two sites.The results indicated an increase in most of the studied characteristics in the summer and autumn season compared to the winter and spring seasons due to the variation in rain rates and temperatures between the seasons. water in Tigris River at the Sharekhan site for all the studied characteristics was of higher quality than that was taken from the AlBusif site to be used for the purposes of (human drinking, plant irrigation, livestock and poultry watering, and fish life). This can attributed to the effect of liquid waste loaded to the River as it passesthrough the city of Mosul.